2013
DOI: 10.1115/1.4024829
|View full text |Cite
|
Sign up to set email alerts
|

Applications of a New Handheld Reference Point Indentation Instrument Measuring Bone Material Strength

Abstract: A novel, hand-held Reference Point Indentation (RPI) instrument, measures how well the bone of living patients and large animals resists indentation. The results presented here are reported in terms of Bone Material Strength, which is a normalized measure of how well the bone resists indentation, and is inversely related to the indentation distance into the bone. We present examples of the instrument's use in: (1) laboratory experiments on bone, including experiments through a layer of soft tissue, (2) three h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 19 publications
0
51
0
Order By: Relevance
“…Apart from BMD, FRAX does not capture other skeletal determinants of bone strength that improve upon or are at least partly independent of aBMD [10]. Several such determinants are the subject of clinical research [11][12][13][14][15][16][17][18] using novel imaging techniques, such as Quantitative Computed Tomography (QCT) and high resolution (peripheral) QCT [19,20], and minimally invasive approaches for probing bone material properties, notably microindentation techniques [21]. Although there is evidence of their predictive ability for fracture [22,23] , none of these modalities appears to reliably outperform aBMD in the prediction of the various types of osteoporotic fractures, and their general lack of availability and validation in the clinical setting means that an adjunctive role alongside DXA-measured aBMD is unlikely to be feasible in most settings in the near future.…”
Section: Osteoporosis Fragility Fractures and Risk Assessmentmentioning
confidence: 99%
“…Apart from BMD, FRAX does not capture other skeletal determinants of bone strength that improve upon or are at least partly independent of aBMD [10]. Several such determinants are the subject of clinical research [11][12][13][14][15][16][17][18] using novel imaging techniques, such as Quantitative Computed Tomography (QCT) and high resolution (peripheral) QCT [19,20], and minimally invasive approaches for probing bone material properties, notably microindentation techniques [21]. Although there is evidence of their predictive ability for fracture [22,23] , none of these modalities appears to reliably outperform aBMD in the prediction of the various types of osteoporotic fractures, and their general lack of availability and validation in the clinical setting means that an adjunctive role alongside DXA-measured aBMD is unlikely to be feasible in most settings in the near future.…”
Section: Osteoporosis Fragility Fractures and Risk Assessmentmentioning
confidence: 99%
“…The availability of a novel microindentation device might now enable the safe measurement of properties of bone material (bone material strength index) in humans. 52,53 Using a prototype device (called a reference point indenter), several small studies found that indices of properties of bone material might be reduced in patients with hip fractures 54 and atypical femoral fractures. 55 The potential utility of this approach for assessing properties of bone material in humans was demonstrated in a proof-of-concept study.…”
Section: Age-related Bone Loss and Fracturesmentioning
confidence: 99%
“…The latter method, impact microindentation, is now utilized in living humans, and is performed using a hand-held RPI device (OsteoProbe® RUO Reference Point Indenter, Active Life Scientific, Santa Barbara, CA, USA) that imparts a single impact load to the bone surface. The handheld OsteoProbe is more amenable for clinical use than the BioDent, which requires a stand to perform measurements in human patients (Randall et al, 2013). Both techniques have been recently reviewed (Allen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%